Problematika Pendidikan Islam di Indonesia Masa Kini - Intan Kusumawardani; Sukari Sukari (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine various problems faced by Islamic education in the modern era, especially related to the challenges arising from globalization, technological developments, and value conflicts. In addition, this study also seeks to identify strategic steps that can be taken to overcome these problems. This study uses a qualitative descriptive approach to analyze the problems faced by Islamic education today. Data were collected through literature studies and document analysis from various official sources. The results of the study are that the problems of Islamic education in the modern era are very diverse, ranging from challenges due to globalization, technological developments, to value conflicts that occur between tradition and modernity. To face these challenges, strategic steps are needed, including improving the quality of the curriculum and teaching, providing more equitable access to education, and using technology wisely to support the learning process. In addition, collaboration between the government, educational institutions, religious figures, and the wider community is key to creating Islamic education that is relevant to the needs of the times but still adheres to the core values of Islam.